The use and modification of injury prevention exercises by professional youth soccer teams - O'Brien, J.; Young, W.; Finch, C. F. (Scandinavian Journal of Medicine & Science in Sports, 2017)
The efficacy of injury prevention exercise programs (IPEPs) for amateur youth soccer has been established, but little is known about their adaptability to other soccer populations. This study aimed to assess the use of individual injury prevention exercises by professional youth soccer teams, against the industry-standard, FIFA 11+ program. Four teams' chosen IPEPs were observed across one season and documented on a standardized form. The use of each FIFA 11+ exercise was coded as "performed", "performed modified" or "not performed". The proportion of the 160 observed sessions containing each individual exercise was calculated. Staff provided reasons for their use and modification of FIFA 11+ exercises. On average, individual FIFA 11+ exercises were conducted in original form in 12% of the sessions (range 0-33%), and in modified form in 28% of sessions (range 2-62%). The five most frequently observed exercises, in either original or modified form, were "bench" (72%), "squats" (69%), "running straight" (68%), "single-leg stance" (66%), and "sideways bench" (64%). Staff modified exercises to add variation, progression, and individualization, and to align with specific training formats and goals. Professional youth soccer teams often use injury prevention exercises similar to those in the FIFA 11+, but tailor them considerably to fit their implementation context.